A Study on Types of Work and Wages in Relation to Age of Child Labor at Rajshahi City - Rahman, ME; lslam, MR; Haque, ME (TAJ: Journal of Teachers Association, 2009)
The study was conducted at Rajshahi city and 180 child workers were selected randomly from different working places such as hotel and restaurant, motor garage, general shops, poultry farm, domestic house, private clinics and private diagnostic centers from January 2009 to March 2009. The study revealed certain variables such as gender, educational level, types of works and wages per month including duration of work of the child workers in relation to their age and the study showed that male were highest in age group 5-9 years and female were highest in age group 13-17 years. The educational level of the respondents was poor in general and in the age group 5-17 years 128 (45.7%) could not read or write at all. The maximum children 44 (15.7%) and 41 (14.6%) respondents were engaged in private diagnostic center and private clinics respectively. The findings could be due to more prevalence of domestic labor at Rajshahi and more prevalence of hotel, private clinics and private diagnostic centers at Rajshahi. Monthly wages of the study respondents was very poor. The study revealed that 54 (19.3%) respondents did not get any wage and they worked for food only. 188 (67.1%) and 38 (13.6%) respondents had wage <500 and in between 500-1000 taka only. The study showed that significant number of children that 238 (85%) had worked more than 8 hours in a day. TAJ 2009; 22(1): 227-230